Neurodevelopmental outcomes after cardiac surgery in infancy - Gaynor, J William; Stopp, Christian; Wypij, David; Andropoulos, Dean B; Atallah, Joseph; Atz, Andrew M; Beca, John; Donofrio, Mary T; Duncan, Kim; Ghanayem, Nancy S; Goldberg, Caren S; Hövels-Gürich, Hedwig; et al. (Pediatrics (Evanston), 2015)
Neurodevelopmental disability is the most common complication for survivors of surgery for congenital heart disease (CHD). We analyzed individual participant data from studies of children evaluated with the Bayley Scales of Infant Development, second edition, after cardiac surgery between 1996 and 2009. The primary outcome was Psychomotor Development Index (PDI), and the secondary outcome was Mental Development Index (MDI). Among 1770 subjects from 22 institutions, assessed at age 14.5 ± 3.7 months, PDIs and MDIs (77.6 ± 18.8 and 88.2 ± 16.7, respectively) were lower than normative means (each P < .001). Later calendar year of birth was associated with an increased proportion of high-risk infants (complexity of CHD and prevalence of genetic/extracardiac anomalies). After adjustment for center and type of CHD, later year of birth was not significantly associated with better PDI or MDI. Risk factors for lower PDI were lower birth weight, white race, and presence of a genetic/extracardiac anomaly (all P ≤ .01). After adjustment for these factors, PDIs improved over time (0.39 points/year, 95% confidence interval 0.01 to 0.78; P = .045). Risk factors for lower MDI were lower birth weight, male gender, less maternal education, and presence of a genetic/extracardiac anomaly (all P < .001). After adjustment for these factors, MDIs improved over time (0.38 points/year, 95% confidence interval 0.05 to 0.71; P = .02). Early neurodevelopmental outcomes for survivors of cardiac surgery in infancy have improved modestly over time, but only after adjustment for innate patient risk factors. As more high-risk CHD infants undergo cardiac surgery and survive, a growing population will require significant societal resources.